1966
DOI: 10.1021/je60030a006
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature PVT Properties of Sodium, Potassium, and Cusium.

Abstract: it is not surprising that they respond similarly toward salt solutions. It appears that secondary amines may be slightly superior to the tertiary amines.Table II and Figure 5 show the results of a study which confirms the validity of the expression K = {K+ K .)12.Gradient quantities of adipic and oleic acid were added to diisopropylamine and equilibrated with 0.1% salt solution.These acids add foreign ions to the system and increase considerably the supply of amine ions.The adipic acid, being water-soluble, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 1 publication
4
43
0
Order By: Relevance
“…All phases of this measurement program have been completed. The final properties of widium (2) and potassium (1) have been published in companion reports; those of cesium are presented in this report.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…All phases of this measurement program have been completed. The final properties of widium (2) and potassium (1) have been published in companion reports; those of cesium are presented in this report.…”
Section: Introductionmentioning
confidence: 94%
“…The possible significance of any thermal ionization in potassium and sodium vapors is discussed in the companion reports (1,2). It was shown that the degree of ionization to be expected in metal vapor may be obtained from its iorization potential (3).…”
Section: Naval Research Laboratorymentioning
confidence: 99%
See 2 more Smart Citations
“…The equation of the straight line representing the particular property was then obtained graphically and used in the computer program. Later, data for sodium compiled by Tokar47 from a number of more recent literature sources became available and, [48][49][50] hence, were used to derive corrected equations for the various properties·. These corrected equations did not differ greatly from the original ones and, therefore, it was not necessary to repeat any of the calculations performed up to that time.…”
Section: Appendix E Physical Properties Of Sodiummentioning
confidence: 99%